2000
DOI: 10.14411/eje.2000.030
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive preferential selection of young coccinellid hosts by the parasitoid wasp Dinocampus coccinellae (Hymenoptera: Braconidae)

Abstract: Abstract.Dinocampus coccinellae females which eclose in mid-summer have the opportunity to oviposit in overwintered or in newly eclosed coccinellid hosts. Given the short further longevity of overwintered hosts, offspring fitness would be increased by ovi positing preferentially in young hosts. Laboratory choice tests show that female D. coccinellae do exhibit such a preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Adult ladybirds are known to secrete volatile chemicals (kairomones) and it is possible that D. coccinellae uses such olfactory signals to locate ladybirds in natural situations. Such host location mechanisms have previously been reported for hymenopteran parasitoids (Sternlicht, 1973;Majerus et al, 2000). However, our results suggest that the wasps initially encounter males and females randomly, so it is unlikely that they are using olfactory tracking to assess the sex of the ladybirds from a distance.…”
Section: Discussionsupporting
confidence: 64%
“…Adult ladybirds are known to secrete volatile chemicals (kairomones) and it is possible that D. coccinellae uses such olfactory signals to locate ladybirds in natural situations. Such host location mechanisms have previously been reported for hymenopteran parasitoids (Sternlicht, 1973;Majerus et al, 2000). However, our results suggest that the wasps initially encounter males and females randomly, so it is unlikely that they are using olfactory tracking to assess the sex of the ladybirds from a distance.…”
Section: Discussionsupporting
confidence: 64%
“…One of the best understood parasitoids is Dinocampus (Perilitus) coccinellae Schrank (Hymenoptera: Braconidae), whose host preference, life history, ecology, and behavior have been thoroughly investigated (Ceryngier and Hodek, 1996;Majerus et al, 2000a;Okuda and Ceryngier, 2000;Al Abassi et al, 2001;Davis et al, 2006;Firlej et al, 2006;Koyama and Majerus, 2008). Adult coccinellids are preferred, especially older females (Majerus et al, 2000a;Davis et al, 2006), but immature parasitoids have been found in host larvae and pupae (Geoghegan et al, 1998). As a solitary endoparasitoid of adults, D. coccinellae prefers larger species of Coccinellinae (Ceryngier and Hodek, 1996).…”
Section: Hymenopterous Parasitoids Of Entomophagous Coccinellidsmentioning
confidence: 99%
“…Few parasitoids of entomophagous coccinellids are specialists, some are widely distribut-ed and attack within a subfamily or tribe (Riddick at al., 2009). One of the best understood parasitoids is Dinocampus (Perilitus) coccinellae Schrank (Hymenoptera: Braconidae), whose host preference, life history, ecology, and behavior have been thoroughly investigated (Ceryngier & Hodek, 1996;Majerus, 1997;Majerus et al, 2000;Okuda & Ceryngier, 2000;Al Abassi et al, 2001;Davis et al, 2006;Firlej et al, 2006;Koyama and Majerus, 2008). In all the biotopes of the Middle Urals and the Southern Urals, we noted the infection of the Coccinellidae larvae, pupae and adults with various species of Parasitica (Hymenoptera).…”
Section: Resultsmentioning
confidence: 89%